2020
DOI: 10.47127/ijtmr.v5i3.104
|View full text |Cite
|
Sign up to set email alerts
|

Banking Sector Competition and Financial Development in Sub-Saharan Africa

Abstract: The study sort to establishing a relationship between banking sector competition and financial development in subSaharan n Africa. The study further disaggregated the data used into Francophone and Anglophone countries, and these were examined separated and compared. Using an annual data on banks across 37 countries in Sub-Saharan Africa spanning the period 2001-2016 and employing the Fixed Effects estimation technique, the study revealed that there is a positive and significant relationship between financial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Although, our results showed a positive effect but practically some domestic banks in Africa are kicked out of the market since they do not have the means to compete with the larger and foreign banks. The positive result is akin to Ricky‐Okine et al (2020) who showed that competition enhances the financial development in SSA. Our finding is inconsistent with that of Carbó et al (2009), who concluded that banking competition could have a negative effect on credit allocation for small firms with information issues.…”
Section: Discussion Of Resultsmentioning
confidence: 83%
“…Although, our results showed a positive effect but practically some domestic banks in Africa are kicked out of the market since they do not have the means to compete with the larger and foreign banks. The positive result is akin to Ricky‐Okine et al (2020) who showed that competition enhances the financial development in SSA. Our finding is inconsistent with that of Carbó et al (2009), who concluded that banking competition could have a negative effect on credit allocation for small firms with information issues.…”
Section: Discussion Of Resultsmentioning
confidence: 83%
“…However, the role of manufacturing and productivity as a source of financial development has been questioned. Ricky-Okine et al (2020) show that recent episodes of financial development acceleration in industrialized countries were driven by productivity advances in the services sector, rather than manufacturing. Nevertheless, the researchers argue that there is no direct link between these findings and financial development.…”
Section: Resultsmentioning
confidence: 96%
“…Ricky-Okine and Amankwaa (2020) investigated how financial development affects economic growth in Ghana from 1960 to 2016 using the ARDL model. They found a long-term correlation between financial development and economic growth, with causation flowing from financial development to economic progress.…”
Section: Review Of Related Literaturementioning
confidence: 99%